Task oriented training improves the balance outcome & reducing fall risk in diabetic population - Ghazal, Javeria (Pak J Med Sci, 2016)
OBJECTIVES: The objective was to determine the balance impairments and to compare task oriented versus traditional balance training in fall reduction among diabetic patients. METHODS: The randomized control trial with descriptive survey and 196 diabetic patients were recruited to assess balance impairments through purposive sampling technique. Eighteen patients were randomly allocated into two groups; task oriented balance training group TOB (n=8) and traditional balance training group TBT (n=10). The inclusion criteria were 30-50 years age bracket and diagnosed cases of Diabetes Mellitus with neuropathy. The demographics were taken through standardized & valid assessment tools include Berg Balance Scale and Functional Reach Test. The measurements were obtained at baseline, after 04 and 08 weeks of training. RESULTS: The mean age of the participants was 49 ±6.79. The result shows that 165(84%) were at moderate risk of fall and 31(15%) were at mild risk of fall among total 196 diabetic patients. There was significant improvement (p <0.05) in task oriented balance training group for dynamic balance, anticipatory balance and reactive balance after 8 weeks of training as compare to traditional balance training. CONCLUSION: Task oriented balance training is effective in improving the dynamic, anticipator and reactive balance. The task oriented training reduces the risk of falling through enhancing balance outcome.